Cost benefits of forest restoration in a tropical grazing landscape: Thiaki rainforest restoration project. (July 2020) - van Oosterzee, Penny; Liu, Hongbo; Preece, Noel D.
Graphical abstract: Highlights: Reforestation of degraded forest lands is vital to sequester greenhouse emissions. Carbon prices have been modeled for minimum value to incentivize reforestation. Few studies have provided real-world costs of reforestation. Farm-level costs and benefits are necessary to encourage farmers to uptake restoration. Carbon prices will need to be much higher to provide positive returns. Abstract: Global forest restoration is vital to mitigate climate change. Tropical forests are under the greatest threat from clearing while offering significant potential for restoration. Forest carbon credits through trading schemes have the potential to enable restoration, providing landholders with incentives to restore forests. Impediments to restoration are numerous, with one of the main ones being the unknown costs of forest restoration and uncertain returns from payment schemes, such as carbon trading programs. Many research and modeling papers on the potential of carbon markets to stimulate reforestation in agricultural landscapes rely on general estimates of reforestation. The reality, though, is that the benefits, returns, and break-even points of the reforestation costs and carbon price are highly sensitive to actual costs. Few papers actually investigate the real costs of farm-level restoration. Nearly all recent papers have used modeled scenarios in calculating Net Present Value (NPV), and so estimates of restoration cost and a return from carbon vary widely depending on modeled assumptions. Real data from a demonstration project in the Wet Tropics of Australia are provided in this paper. Three land use scenarios are compared: carbon only, cattle only, and a combination of carbon and cattle using on-ground data for restoration. Not surprisingly, scenarios of the highest carbon prices generate the highest net benefits in both carbon only and mixed carbon and cattle scenarios. A minimum carbon price of AUD$37 per ton of carbon dioxide equivalent is required to match income derived from cattle. The current policy environment that rewards the lowest cost abatement runs counter to Australia playing its role in the urgent need to limit global temperature rise to 2 degrees Celsius and preferably 1.5 degrees Celsius.